A three-legged stool: Teachers' views of Junior Cycle Physical Education curriculum change. (May 2022) - O'Sullivan, Mary; Moody, Brigitte; Parker, Melissa; Carey, Michael
The purpose of this paper was to examine Irish Physical Education teachers' views on curriculum change at the beginning of its implementation stage, with a particular focus on revision to the Physical Education curriculum and the new Wellbeing programme. In the light of these revisions, teachers were asked to make considerable changes to their beliefs and pedagogical approaches. Teacher change theory provided a lens through which to examine teachers' views. We reimaged the three aspects of teacher change as a triangle or 'three-legged stool' where the three elements of curriculum materials/resources, pedagogy, and beliefs combine to offer a sense of security to sustain the impending changes. A survey and a series of semi-structured interviews provided data and in total 119 second level Physical Education teachers participated. Analysis was conducted using descriptive statistics of quantitative data and inductive and deductive analysis of qualitative data. Three themes were developed: A Learning Focus, Embracing Change, and Curriculum Enactment. Contrary to recent findings in the change literature, the teachers in this study welcomed curriculum changes as their beliefs aligned with the purpose of the reform of Physical Education. The results indicated that the new curriculum was catching up with teachers' core beliefs about the purpose of Physical Education. However, in line with recent research, teachers were sceptical about ongoing support for resourcing and continued professional development. In conclusion, the 'three-legged stool of sustained change has the potential to be unbalanced thereby maintaining teacher buy-in to the new reforms is potentially fragile.